Nanometer pocket structure for capturing target molecules and preparation method and application thereof

By designing the nanopocket structure, using magnetic iron tetraoxide particles and mesoporous silica layer to combine nano-gold branches, the problem of difficult positioning of target molecules in SERS technology is solved, and high sensitivity detection of extremely low concentration drugs is achieved.

CN119191367APending Publication Date: 2024-12-27SHANGHAI CRIMINAL SCI TECH RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324533.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

When existing SERS technology detects target molecules at very low concentrations, it is difficult for analytes to accurately locate the plasma hot spot area, resulting in limited detection sensitivity.

Method used

Design a nanopocket structure, using magnetic iron tetraoxide particles as the substrate, coated with a mesoporous silica layer of polysilanol groups, and loaded nano-gold branches in its pores to form an efficient SERS substrate to ensure the target molecule Can be accurately captured and concentrated in the enhancement area.

Benefits of technology

It significantly improves detection sensitivity and can detect extremely low concentrations of drug molecules, providing efficient drug detection methods, especially in the field of low concentration detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191367A_ABST
    Figure CN119191367A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic nano gold branch materials, and particularly provides a nano pocket structure for capturing target molecules as well as a preparation method and application of the nano pocket structure, the nano pocket structure comprises magnetic ferroferric oxide particles serving as a substrate and a multi-silanol group mesoporous silica layer coating the substrate; wherein nano gold branches are loaded in pore channels of the mesoporous silica. The nano pocket structure can be used for constructing an SERS (Surface Enhanced Raman Scattering) substrate for detecting drugs with high sensitivity, target molecules are accurately captured to a plasma hot spot area, and detection of drug molecule Raman scattering signals with extremely low concentration (10 <-9 > M) is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic nano-gold dendrite materials, and in particular to a nano-pocket structure for capturing target molecules, and a preparation method and application thereof. Background Art

[0002] How to quickly and sensitively detect trace amounts of drugs is crucial to combating drug crimes and maintaining social stability. Conventional drug detection and analysis methods include gas chromatography, liquid chromatography-mass spectrometry, nuclear magnetic resonance spectroscopy, DNA aptamer sensors, capillary electrophoresis or immunoassays. However, most traditional methods have problems such as cumbersome sample pretreatment, high detection cost, long time consumption, and high technical barriers. Therefore, the development of a fast, accurate, and highly sensitive on-site drug detection method is of great significance to public security drug control work. Surface-Enhanced Raman Scattering (SERS) analysis technology is more suitable for actual on-site drug detection due to its advantages such as high sensitivity, good portability, and simple operation.

[0003] It should be noted that surface enhanced Raman scattering is a technology that uses the local surface plasmon resonance effect generated on the surface of metal nanomaterials (such as gold or silver) to enhance the Raman scattering signal. By adsorbing the molecules to be tested on metal nanoparticles or their surfaces, SERS significantly increases the intensity of Raman scattering, allowing low concentrations of molecules to be detected. This enhancement effect makes SERS a highly sensitive analytical technology with wide applications in biosensing, environmental monitoring, and materials science.

[0004] SERS-based molecular detection usually uses noble metal nanostructures as plasmonic optical antennas to stimulate strong local electromagnetic field enhancement. The main research direction focuses on the preparation of plasmonic nanostructures with tiny nanogaps, such as nanoparticle assemblies, dimer antennas, and nanotip / gap arrays, to improve SERS performance by adjusting the nanoparticle spacing. However, as the gap approaches the quantum effect scale, it becomes increasingly difficult for analytes to enter the plasmonic hotspot area, and it is even more difficult to accurately locate the analyte in the tip area, which fundamentally limits the application of SERS analysis technology. Summary of the invention

[0005] To this end, the embodiments of the present application provide a nano-pocket structure for capturing target molecules and a preparation method and application thereof. The nano-pocket structure can construct a SERS substrate for highly sensitive drug detection, accurately capture target molecules in the plasma hotspot area, and is conducive to detecting extremely low concentrations (10 -9 M) Raman scattering signal of drug molecules.

[0006] The following technical solutions are adopted in the embodiments of the present application:

[0007] A nano-pocket structure for capturing target molecules comprises magnetic ferrosoferric oxide particles as a substrate and a mesoporous silica layer of multi-silanol groups coated outside the substrate; wherein nano-gold branches are loaded in the pores of the mesoporous silica.

[0008] In this embodiment, the traditional SERS substrate is easily limited when processing tiny gaps close to the quantum effect scale, and it is difficult for the target molecule to be accurately located in the plasma hotspot. This solution effectively solves this problem through the design of the nano-pocket structure, so that the target molecule can be accurately captured and concentrated in the enhanced area.

[0009] Specifically, ferroferric oxide (Fe3O4) is a magnetic material that provides support and stability as a substrate. Its magnetic properties can also make it easy to separate and manipulate nanostructures during preparation and detection. The mesoporous silica layer coated on the outside of the ferroferric oxide particles provides a rich pore structure and an effective molecular capture site, which can effectively improve the surface adsorption and capture ability of the target molecule, and the polysilanol group enhances the interaction between the mesoporous silica and the target molecule, thereby improving the selectivity and capture efficiency. In this embodiment, the magnetism of ferroferric oxide and the high surface area of ​​mesoporous silica are combined, so that the nano pocket structure can efficiently capture the target molecule. By optimizing the functionalization of the polysilanol group, the selective capture of specific molecules can be further improved. The nano gold branches loaded in the mesoporous silica pores are the key to introducing the SERS effect. The nano gold branches have a unique shape and high local electromagnetic field enhancement ability, and can form a powerful SERS hotspot around them. The nanogold branches in this embodiment can provide enough hot spots to improve the SERS performance. When the target molecules bind to these hot spots, their Raman scattering signals are significantly enhanced, thereby improving the detection sensitivity and even detecting target molecules at very low concentrations.

[0010] The nano-pocket structure of the present application creates an efficient SERS substrate by coating a mesoporous silica layer with multiple silanol groups on the outside of the magnetic ferroferric oxide particles and loading nano-gold branches in the pores of the mesoporous silica. The nano-pocket structure can not only achieve efficient capture of target molecules, but also enhance Raman signals and improve detection sensitivity. The technical solution of the present application has shown significant advantages in high-sensitivity detection applications, especially in the field of low-concentration drug detection, showing its important application value.

[0011] As a feasible implementation method, the particle size of the magnetic ferroferric oxide particles is in the range of 50 to 500 nm, and the thickness of the mesoporous silica is in the range of 10 to 150 nm.

[0012] In some embodiments, the particle size range of the magnetic ferroferric oxide particles is 50-100nm, 50-200nm, 50-400nm, 100-200nm, 100-400nm, 100-500nm, 200-400nm, 200-500nm, 400-500nm.

[0013] In a specific embodiment, the particle size of the magnetic ferroferric oxide particles can be 500, 400, 200, 100 or 50 nm.

[0014] In some embodiments, the mesoporous silica has a thickness of 10-30 nm, 10-40 nm, 30-40 nm, 30-150 nm, or 40-150 nm.

[0015] In a specific embodiment, the thickness of the mesoporous silica is 10 nm, 30 nm, 40 nm or 150 nm.

[0016] In this embodiment, the particle size of the ferrosoferric oxide particles is in the range of 50 to 500 nm, which can effectively maintain its magnetic characteristics. These particles have superparamagnetism, which enables them to quickly adsorb target molecules under the action of an external magnetic field, and remain suspended after the magnetic field is removed, which is convenient for subsequent separation and detection. The particle size in the range of 50 to 500 nm can provide a good surface area to volume ratio, while avoiding the difficulty of handling caused by too small particle size and the ease of operation affected by too large particle size. The particles within this range have good stability in the mesoporous silica layer, which helps to maintain the stability and function of the overall structure. When these magnetic particles are combined with the mesoporous silica layer and nano-gold branches as a substrate, they can play a comprehensive role in molecular capture, plasma enhancement and signal detection. The appropriate particle size ensures a high surface activity, and the SERS performance can be optimized by adjusting the particle size. Specifically, the optimized particle size can effectively support the integration of the mesoporous structure and the nano-gold branches, and improve the signal intensity and detection sensitivity of SERS.

[0017] At a thickness of 10 to 150 nm, mesoporous silica maintains good structural stability and mechanical strength. At the same time, at this thickness, the pore size distribution is relatively uniform, which helps to improve its effect in adsorbing target molecules and integrating nanogold branches. In other words, the ability to capture target molecules can be controlled by adjusting the thickness of the silicon layer.

[0018] As a feasible implementation method, nano-gold colloid particles are adsorbed on the surface of the magnetic ferrosoferric oxide particles, and the nano-gold branches are obtained by growing the nano-gold colloid particles as gold seeds in the pores of the mesoporous silica.

[0019] In this embodiment, nano gold colloid particles are deposited on the surface of ferroferric oxide particles as gold seeds through chemical reactions in the solution. These colloid particles provide the starting seeds of gold and provide the base core for the subsequent growth of gold branches. The mesoporous silica layer is coated on the surface of the ferroferric oxide particles, providing an ordered pore structure for the growth of gold branches. At the same time, the surface of the mesoporous silica layer can enhance its binding ability with the target molecule through chemical modification of multi-silanol groups, and provide a stable environment to promote the growth of nano gold branches. Nano gold colloid particles are used as gold seeds, and further grow into nano gold branches through reduction reactions in the pores of mesoporous silica. The growth of nano gold branches is usually achieved through a chemical reduction process, in which gold ions are reduced and grow on the surface of gold colloid particles to form nano dendrite structures, for example, chloroauric acid is reduced on the surface of nano gold colloid particles to grow nano gold branches. These nano gold branches have a significant surface plasmon resonance effect, which can form a local strong electromagnetic field at its tip or gap, significantly enhancing the surface enhanced Raman scattering (SERS) signal and improving the detection sensitivity.

[0020] As a feasible implementation mode, the particle size of the nano-gold colloidal particles ranges from 3 to 15 nm.

[0021] In some embodiments, the particle size of the nano-gold colloidal particles ranges from 3 to 5 nm, 3 to 10 nm, 5 to 10 nm, 5 to 15 nm, and 10 to 15 nm.

[0022] In a specific embodiment, the particle size of the nano-gold colloidal particles is 3nm, 5nm, or 10nm.

[0023] In this embodiment, the size of the nano-gold colloidal particles is in the range of 3 to 15 nm, which is conducive to uniform distribution in the mesoporous silica pores. At the same time, the nano-gold colloidal particles of the above particle size, as seeds of gold branches, have a large surface atomic ratio, which enhances their reactivity and is conducive to forming a uniform nano-gold branch structure in the mesoporous silica pores.

[0024] In a second aspect, the present application also provides a method for preparing a nano-pocket structure for capturing target molecules, characterized in that it comprises the following steps:

[0025] Step 1: preparing Fe3O4@PEI nanomaterials: adding Fe3O4 magnetic particles to a polyethyleneimine aqueous solution, and subjecting the solution to ultrasonic reaction to allow polyethyleneimine to self-assemble on the surface of the Fe3O4 magnetic particles to form Fe3O4@PEI particles;

[0026] Step 2, preparing Fe3O4@Au nanomaterials: adding Fe3O4@PEI nanomaterials into nano-gold colloids, and ultrasonically reacting the nano-gold colloids to adsorb the colloidal gold particles onto the surface of the Fe3O4@PEI particles, thereby obtaining Fe3O4@Au nanomaterials;

[0027] Step 3, preparing Fe3O4@Au@mSiO2 nanomaterials: ultrasonically disperse the Fe3O4@Au nanomaterials into a hexadecyltrimethylammonium bromide aqueous solution, slowly drop tetraethyl silicate after adding alkali, react for 24 hours after the addition is completed, separate by magnetic adsorption, and wash the solids three times with water and ethanol respectively; disperse the obtained solids in a template removal solution and stir for 8 hours, and repeat the operation several times to obtain Fe3O4@Au@mSiO2 nanomaterials;

[0028] Step 4. Preparation of Fe3O4@mSiO2@bAu nanomaterials: Ultrasonic dispersion of Fe3O4@Au@mSiO2 nanomaterials in water, adding chloroauric acid solution and dilute hydrochloric acid, followed by silver nitrate solution and ascorbic acid solution, reacting at room temperature, separating by magnetic adsorption, and then washing the solid three times with water and ethanol respectively.

[0029] In this embodiment, Fe3O4 magnetic particles are mixed with polyethyleneimine (PEI) aqueous solution by ultrasound, so that PEI is self-assembled on the surface of Fe3O4 to form a composite material. The presence of PEI enhances the surface activity and functionalization ability of Fe3O4 magnetic particles and improves its adhesion to other materials. Fe3O4@Au nanomaterials are mixed with nanogold colloids, and nanogold particles are attached to the surface of Fe3O4@PEI particles by physical adsorption. The introduction of gold particles increases the surface functionality and provides additional enhancement effects (such as signal enhancement of surface plasmon resonance in SERS detection). A layer of mesoporous silica (mSiO2) is further coated on the surface of Fe3O4@Au nanomaterials, and a silanization agent is introduced using a sol-gel method. The introduction of mesoporous silica increases the specific surface area of ​​the particles, provides a larger reaction surface for subsequent functionalization, and improves the stability of the material. The growth of gold nanowires is completed in the pores of the Fe3O4@Au@mSiO2 nanomaterials by adding chloroauric acid solution and dilute hydrochloric acid, followed by silver nitrate solution and ascorbic acid solution, to fully react and form gold nanowires. These gold nanowires can provide sufficient hot spots to improve SERS performance.

[0030] As a feasible implementation method, the Fe3O4 magnetic particles in step 1 are prepared by solvent thermal synthesis, with a particle size range of 50 to 500 nm; the concentration of the polyethyleneimine aqueous solution is 0.1% to 1%; and the ultrasonic reaction time is 10 to 60 min.

[0031] In this embodiment, the solvent thermal synthesis method dissolves the raw materials in a solvent to form high-quality Fe3O4 magnetic particles by reacting under high temperature and high pressure conditions. The reason is that the solvent thermal synthesis method can control the particle size and morphology of the particles, ensuring the uniformity and performance consistency of the Fe3O4 magnetic particles. The particle size range is 50 to 500nm, which makes the particles have good magnetism and operability. A 0.1% to 1% concentration of PEI aqueous solution is used to functionalize the Fe3O4 particles. PEI is a multifunctional polymer that can be effectively attached to the surface of magnetic particles, providing good dispersibility and surface modification functions. Ultrasonic treatment for 10 to 60 minutes helps to evenly disperse the Fe3O4 particles and promote the attachment of PEI.

[0032] Exemplarily, the specific steps of preparing Fe3O4 magnetic particles by solvent thermal synthesis may include:

[0033] Prepare a solution containing 0.2M ferric chloride (FeCl3), sodium citrate and sodium acetate, with ethylene glycol as the solvent. Add the prepared solution to the reactor, set the reaction temperature to 200°C, and the reaction time to 10 hours. Perform a heating reaction in a closed reactor. Under high temperature and pressure, the iron ions will be reduced to form Fe3O4 particles. After the reaction is completed, cool to room temperature and use a centrifuge to separate the Fe3O4 particles. Wash the particles with deionized water and ethanol to remove unreacted precursors and impurities. Dry the washed particles in a vacuum drying oven to obtain dry Fe3O4 magnetic particles.

[0034] As a feasible implementation method, the size of the nano-gold colloid particles in step 2 is 3 to 15 nm; and the ultrasonic reaction time is 10 to 60 min.

[0035] In this embodiment, the size of the nano-gold colloid particles is in the range of 3 to 15 nm, which is conducive to forming a uniform nano-gold dendrite structure in the mesoporous silica pores. 10 to 60 minutes of ultrasonic treatment helps to evenly disperse the gold colloid particles and improve the stability of the particles. Ultrasonic waves can reduce the aggregation between particles and ensure uniform distribution of particles.

[0036] As an achievable implementation method, the concentration of the hexadecyltrimethylammonium bromide aqueous solution in step three is 0.01% to 1%; the base includes any one of triethylamine, 25% ammonia water, 15% ammonia water, 5% ammonia water, triethanolamine, 0.1M sodium hydroxide, 0.5M sodium hydroxide, and 1M sodium hydroxide; the weight of the tetraethyl silicate is 5 to 100 times that of the Fe3O4@Au nanomaterial; the reaction temperature is 25 to 100 degrees; the template removal solution is ethanol, 1% HCl / ethanol, 1% NaCl / methanol, 0.6% ammonium nitrate solution or acetone, and the number of template removal times is 5 to 8 times.

[0037] In this embodiment, hexadecyltrimethylammonium bromide (CTAB): CTAB forms micelles in the reaction system, and these micelles, in the presence of a silicon source (such as tetraethyl silicate), cause silicon dioxide to be deposited on its surface to form an ordered mesoporous structure. By adjusting the concentration of CTAB, the size and distribution of the mesopores can be controlled. By controlling the concentration of the silicon source and the reaction conditions, a uniform silicon dioxide coating can be achieved, improving the performance and stability of the material. The pH value of the reaction can be adjusted using an alkaline solution (such as triethylamine, ammonia water, sodium hydroxide, etc.), thereby controlling the gelation rate and structure of silicon dioxide. Different concentrations of alkali will affect the formation rate of silicon dioxide and the thickness of the film.

[0038] Tetraethyl silicate (TEOS) is used as a silicon source, and the mass ratio of Fe3O4@Au nanomaterials is 5 to 100 times, ensuring sufficient silicon source supply to form a silica coating layer. This ratio helps to control the thickness and uniformity of the coating layer. For example, by adjusting the ratio of TEOS to Fe3O4@Au, the thickness of the silica layer can be precisely controlled, thereby adjusting the properties of the material (such as magnetic and optical properties). The temperature range of 25 to 100 ° C can optimize the reaction rate and the deposition rate of silica, affecting the structure and properties of the final material. Ethanol, 1% HCl / ethanol, 1% NaCl / methanol, 0.6% ammonium nitrate solution or acetone in the template removal solution are used to remove templates such as CTAB. These solutions effectively remove the template through different chemical forces (such as acidity and salt ion effects), leaving a silica structure with the expected pore size. The number of template removals (5 to 8 times): Multiple template removals can ensure the complete removal of template materials, reduce impurities, and obtain high-purity mesoporous silica structures. The optimized coating and pore structure increase the surface area and functionality of the material to enhance the adsorption of target molecules.

[0039] As a feasible implementation method, the concentration of the chloroauric acid solution in step 4 is 0.1M to 1M; the concentration of the dilute hydrochloric acid is 0.1M to 2.5M; the concentration of the silver nitrate solution is 1mM to 10mM; the concentration of the ascorbic acid solution is 0.05M to 1M; and the reaction time is 10 to 60min.

[0040] In this embodiment, chloroauric acid solution (0.1M~1M) provides gold ions (Au3+), which are converted into nano-gold branches during the reduction process. Dilute hydrochloric acid (0.1M~2.5M) is used to adjust the pH value of the solution, which helps to control the rate and stability of the reduction reaction. Silver nitrate solution (1mM~10mM) is used to provide auxiliary silver ions to form stable nano-gold branches. Ascorbic acid (0.05M~1M) is used as a reducing agent to reduce gold ions to nano-gold branches. Reaction time (10~60min), the reaction time affects the size and distribution of the particles, and the appropriate time can control the growth and morphology of nanoparticles. Using ascorbic acid as a reducing agent, the reaction speed is faster, and high-quality nano-gold branches can be generated in a shorter time. By precisely controlling the reaction conditions, efficient and stable generation of nano-gold branches can be achieved.

[0041] In a third aspect, the embodiments of the present application also provide the application of the nano-pocket structure described in the first aspect in Raman spectroscopy detection of drugs.

[0042] In summary, the present invention provides a nano-pocket structure for capturing target molecules, wherein the nano-pocket structure is composed of magnetic ferroferric oxide coated with multi-silanol group mesoporous silica having target molecule capture sites, and the nano-gold branches loaded in the pores of the mesoporous silica can provide sufficient hot spots for improving SERS performance. The nano-pocket structure described in the present application is used to detect trace methamphetamine, α-methyltryptamine and edonisine in water, with low detection limit, satisfactory linear range, good uniformity and stability, indicating that the nano-pocket structure has great application potential in drug detection, and also provides the possibility for the reuse and recycling of SERS substrates. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A schematic diagram of a process for preparing a nano-pocket structure for capturing target molecules provided in an embodiment of the present application;

[0044] Figure 2 Characterization diagrams of the preparation process of the nano-pocket structure of Example 1 of the present application, wherein (ac) are scanning electron microscope images (SEM) of Fe3O4@Au, Fe3O4@Au@mSiO2 and Fe3O4@mSiO2@bAu, and (df) are transmission electron microscope images (TEM) of Fe3O4@Au, Fe3O4@Au@mSiO2 and Fe3O4@mSiO2@bAu, respectively;

[0045] Figure 3 This is an elemental surface scanning diagram of the nano-pocket structure Fe3O4@mSiO2@bAu of Example 1 of the present application;

[0046] Figure 4This is the adsorption curve of different materials during the preparation process of Example 1 of the present application;

[0047] Figure 5 A schematic diagram of a SERS detection application of a nano-pocket structure for capturing target molecules provided in an embodiment of the present application;

[0048] Figure 6 The SERS spectra of the nano-pocket structure in Example 1 of the present invention are used to detect different concentrations of methamphetamine, α-methyltryptamine and etonizine. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0050] It should be understood that the scope of protection of the present application is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present application are for describing specific embodiments rather than for limiting the scope of protection of the present application.

[0051] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present application, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present application have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present application, any method, equipment, and material of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present application can also be used to realize the present application.

[0052] It is particularly noted that, unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents used, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0053] In the description of this specification, the "room temperature" has a well-known meaning in the art, generally referring to 24-28° C. The reference term "M" is a concentration unit, representing moles per liter (mol / L). The reference term "mM" is a concentration unit, representing millimoles per liter (mmol / L).

[0054] Each "reaction temperature" in the present application refers to the temperature of each reaction liquid system in each synthesis step.

[0055] In molecular detection based on SERS (surface enhanced Raman scattering), noble metal nanostructures (such as gold or silver) are often used as plasmon optical antennas to excite strong local electromagnetic fields. This strong electromagnetic field significantly enhances the Raman scattering signal, making it feasible to detect molecules at low concentrations. The main research directions of SERS substrates are: Nanoparticle assembly: a structure formed by arranging multiple nanoparticles together. Dimer antenna: a structure composed of two nanoparticles, this configuration can produce a stronger local electromagnetic field. Nanotip / gap array: a structure formed at the tip and the gap, which usually produces the strongest local electromagnetic field. The above directions all improve the SERS performance by adjusting the spacing between nanoparticles.

[0056] However, when the nanogap becomes very small, approaching the scale of quantum effects, it is difficult for molecules to enter these extremely small spaces. This is because the changes in the electromagnetic field become more complex at the scale of quantum effects, and the diffusion and entry of molecules become more restricted. In addition, in the nanotip region, due to the intensity of the electromagnetic field and the extreme compression of space, the analyte needs to be accurately located in the area with the strongest electromagnetic field (i.e., the hot spot area) to be effectively detected. The extremely small gap restricts the entry of molecules and reduces the contact between the analyte and the plasma hot spot area, thereby reducing the sensitivity of the detection. Therefore, these problems limit the application of SERS technology in extremely high sensitivity detection, especially when extremely small gaps are required to achieve a strong enhancement effect.

[0057] To this end, the present application discloses a nano-pocket structure for capturing target molecules, a preparation method thereof, and an application thereof, wherein the nano-pocket structure comprises magnetic ferroferric oxide particles as a substrate and a mesoporous silica layer with multiple silanol groups; nano-gold branches are loaded in the pores of the mesoporous silica. The nano-pocket structure particles provided by the present invention are easy to prepare, have good uniformity and stability, utilize the mesoporous silica layer with multiple silanol groups to capture target molecules into the mesopores, and the nano-gold branches loaded in the pores of the silica provide plasma hotspot areas, thereby achieving the purpose of high-sensitivity drug detection, and providing strong support for the public security drug control work.

[0058] Example 1

[0059] Figure 1 A schematic diagram of a process for preparing a nano-pocket structure for capturing target molecules provided in an embodiment of the present application. Figure 1 As shown, this embodiment 1 relates to a method for preparing a nano-pocket structure for capturing target molecules, which specifically includes:

[0060] Step 1) Preparation of Fe3O4@PEI nanomaterials: 0.5 g of Fe3O4 magnetic particles (particle size of 400 nm) were added to 100 mL of 0.5% polyethyleneimine (PEI) aqueous solution and ultrasonicated for 30 min to allow PEI to self-assemble on the surface of Fe3O4 magnetic particles to form Fe3O4@PEI particles. After magnetic separation, the Fe3O4@PEI particles were washed with deionized water 5 times.

[0061] Step 2) Preparation of Fe3O4@Au nanomaterials: Add the prepared Fe3O4@PEI nanomaterials to 500 mL of nanogold (particle size 5 nm) colloid, ultrasonically react for 30 min to allow the colloidal gold particles to adsorb to the surface of the Fe3O4@PEI particles, and wash with deionized water 5 times after magnetic separation to obtain the Fe3O4@Au nanomaterials.

[0062] Step 3) Preparation of Fe3O4@Au@mSiO2 nanomaterials: ultrasonically disperse 0.1 g of Fe3O4@Au nanomaterials into 500 mL of 0.2% hexadecyltrimethylammonium bromide (CTAB) aqueous solution, add 10 mL of 25% ammonia aqueous solution, slowly drop 2 mL of tetraethyl silicate, and complete the dropwise addition within 30 min. React at 45 degrees for 24 hours. After magnetic adsorption separation, wash the solid three times with water and ethanol respectively; disperse the obtained solid in 100 mL of ethanol solution and reflux for 8 hours. Repeat the operation 5 times. After magnetic separation, wash with water and ethanol three times to obtain Fe3O4@Au@mSiO2 nanomaterials.

[0063] Step 4) Preparation of Fe3O4@mSiO2@bAu nanomaterials: Ultrasonic dispersion of 5 mg of Fe3O4@Au@mSiO2 nanomaterials in 10 mL of deionized water, addition of 50 mL of 0.25 mM chloroauric acid solution and 1 mL of 0.1 M dilute hydrochloric acid, followed by sequential addition of 1 mL of 5 mM silver nitrate solution and 1 mL of 0.3 M ascorbic acid solution, reaction at room temperature for 30 min, separation by magnetic adsorption, washing the solid three times with water and ethanol respectively, and naturally drying to obtain Fe3O4@mSiO2@bAu nanomaterials.

[0064] Figure 2 This is a characterization diagram of the preparation process of the nano-pocket structure in Example 1 of this application. Figure 2 As shown, Figure 2 (ac) are scanning electron microscope images (SEM) of Fe3O4@Au prepared in step 2) of Example 1, Fe3O4@Au@mSiO2 prepared in step 3) and Fe3O4@mSiO2@bAu prepared in step 4), respectively. Figure 2(d-f) are transmission electron microscopy (TEM) images of Fe3O4@Au prepared in step 2), Fe3O4@Au@mSiO2 prepared in step 3), and Fe3O4@mSiO2@bAu prepared in step 4). From the TEM results, it can be seen that the particle size of Fe3O4 particles is about 400nm, and the thickness of the outer mesoporous silica layer is 30-40nm.

[0065] Figure 3 The elemental surface scanning diagram of the overall and local Fe3O4@mSiO2@bAu nano-pocket structure prepared in step 4) of this embodiment 1. Figure 3 It can be seen that gold branches grow in the pores of the prepared nano-pocket structure mesoporous silica, and there are gaps between the gold branches, indicating that the pocket structure prepared by the present invention has a Raman enhanced hotspot.

[0066] Example 2

[0067] This embodiment 2 relates to a method for preparing a nano-pocket structure for capturing target molecules, which specifically includes:

[0068] Step 1) Preparation of Fe3O4@PEI nanomaterials: 0.5 g Fe3O4 magnetic particles (~200 nm) were added to 100 mL 0.5% PEI aqueous solution and ultrasonicated for 30 min to allow PEI to self-assemble on the surface of Fe3O4 magnetic particles to form Fe3O4@PEI particles. After magnetic separation, the Fe3O4@PEI particles were washed with deionized water for 5 times.

[0069] Step 2) Preparation of Fe3O4@Au nanomaterials: Add the prepared Fe3O4@PEI nanomaterials into 200 mL of nanogold (~10 nm) colloid, and ultrasonically react for 30 min to allow the colloidal gold particles to adsorb onto the surface of the Fe3O4@PEI particles. After magnetic separation, wash with deionized water 5 times to obtain the Fe3O4@Au nanomaterials.

[0070] Step 3) Preparation of Fe3O4@Au@mSiO2 nanomaterials: ultrasonically disperse 0.1g of Fe3O4@Au nanomaterials into 500mL of 0.2% CTAB aqueous solution, add 10mL of 0.1M sodium hydroxide solution, slowly drop 1mL of tetraethyl silicate, and complete the dropwise addition within 30min. React at 45 degrees for 24 hours. After magnetic adsorption separation, wash the solid three times with water and ethanol respectively; disperse the obtained solid in 100mL of ethanol solution and reflux for 8 hours. Repeat the operation 5 times. After magnetic separation, wash with water and ethanol three times to obtain Fe3O4@Au@mSiO2 nanomaterials.

[0071] Step 4) Preparation of Fe3O4@mSiO2@bAu nanomaterials: Ultrasonic dispersion of 2 mg of Fe3O4@Au@mSiO2 nanomaterials in 10 mL of deionized water, addition of 50 mL of 0.25 mM chloroauric acid solution and 1 mL of 0.1 M dilute hydrochloric acid, followed by sequential addition of 1 mL of 5 mM silver nitrate solution and 1 mL of 0.3 M ascorbic acid solution, reaction at room temperature for 30 min, separation by magnetic adsorption, washing the solid three times with water and ethanol respectively, and naturally drying to obtain Fe3O4@mSiO2@bAu nanomaterials.

[0072] Example 3

[0073] This embodiment relates to a method for preparing a nano-pocket structure for capturing target molecules, which specifically includes:

[0074] Step 1) Preparation of Fe3O4@PEI nanomaterials: 0.5 g Fe3O4 magnetic particles (~100 nm) were added to 200 mL 0.1% PEI aqueous solution and ultrasonicated for 30 min to allow PEI to self-assemble on the surface of Fe3O4 magnetic particles to form Fe3O4@PEI particles. After magnetic separation, the Fe3O4@PEI particles were washed with deionized water for 5 times.

[0075] Step 2) Preparation of Fe3O4@Au nanomaterials: Add the prepared Fe3O4@PEI nanomaterials to 500 mL of nanogold (~3 nm) colloid, and ultrasonically react for 30 min to allow the colloidal gold particles to adsorb onto the surface of the Fe3O4@PEI particles. After magnetic separation, wash with deionized water 5 times to obtain the Fe3O4@Au nanomaterials.

[0076] Step 3) Preparation of Fe3O4@Au@mSiO2 nanomaterials: ultrasonically disperse 0.1g of Fe3O4@Au nanomaterials into 1000mL of 0.1% CTAB aqueous solution, add 10mL of triethylamine, slowly drop 4mL of tetraethyl silicate, and complete the dropwise addition within 30min. React at 60 degrees for 24 hours. After magnetic adsorption separation, wash the solid three times with water and ethanol respectively; disperse the obtained solid in 100mL of ethanol solution and reflux for 8 hours. Repeat this operation 5 times. After magnetic separation, wash it 3 times with water and ethanol respectively to obtain Fe3O4@Au@mSiO2 nanomaterials.

[0077] Step 4) Preparation of Fe3O4@mSiO2@bAu nanomaterials: Ultrasonic dispersion of 5 mg of Fe3O4@Au@mSiO2 nanomaterials in 10 mL of deionized water, addition of 100 mL of 0.25 mM chloroauric acid solution and 1 mL of 1 M dilute hydrochloric acid, followed by sequential addition of 1 mL of 10 mM silver nitrate solution and 1 mL of 0.5 M ascorbic acid solution, reaction at room temperature for 30 min, separation by magnetic adsorption, washing the solid three times with water and ethanol respectively, and naturally drying to obtain Fe3O4@mSiO2@bAu nanomaterials.

[0078] Example 4

[0079] This embodiment relates to a method for preparing a nano-pocket structure for capturing target molecules, which specifically includes:

[0080] Step 1) Preparation of Fe3O4@PEI nanomaterials: 0.5 g Fe3O4 magnetic particles (~50 nm) were added to 50 mL 0.5% PEI aqueous solution and ultrasonicated for 30 min to allow PEI to self-assemble on the surface of Fe3O4 magnetic particles to form Fe3O4@PEI particles. After magnetic separation, the Fe3O4@PEI particles were washed with deionized water for 5 times.

[0081] Step 2) Preparation of Fe3O4@Au nanomaterials: Add the prepared Fe3O4@PEI nanomaterials to 50 mL of nanogold (~5 nm) colloid, and ultrasonically react for 30 min to allow the colloidal gold particles to adsorb onto the surface of the Fe3O4@PEI particles. After magnetic separation, wash with deionized water 5 times to obtain the Fe3O4@Au nanomaterials.

[0082] Step 3) Preparation of Fe3O4@Au@mSiO2 nanomaterials: ultrasonically disperse 0.1g of Fe3O4@Au nanomaterials into 100mL of 0.1% CTAB aqueous solution, add 10mL of triethanolamine, slowly drop 0.5mL of tetraethyl silicate, and complete the dropwise addition within 30min. React at 45 degrees for 24 hours. After magnetic adsorption separation, wash the solid three times with water and ethanol respectively; disperse the obtained solid in 100mL of acetone solution and reflux for 8 hours. Repeat the operation 7 times. After magnetic separation, wash it 3 times with water and ethanol respectively to obtain Fe3O4@Au@mSiO2 nanomaterials.

[0083] Step 4) Preparation of Fe3O4@mSiO2@bAu nanomaterials: Ultrasonic dispersion of 5 mg of Fe3O4@Au@mSiO2 nanomaterials in 10 mL of deionized water, addition of 80 mL of 0.25 mM chloroauric acid solution and 0.5 mL of 1 M dilute hydrochloric acid, followed by sequential addition of 2 mL of 5 mM silver nitrate solution and 2 mL of 0.3 M ascorbic acid solution, reaction at room temperature for 30 min, separation by magnetic adsorption, washing the solid three times with water and ethanol respectively, and naturally drying to obtain Fe3O4@mSiO2@bAu nanomaterials.

[0084] Example 5

[0085] The Fe3O4@Au, Fe3O4@Au@mSiO2, and Fe3O4@mSiO2@bAu nanomaterials prepared in Example 1 were tested for their ability to capture methamphetamine target molecules. 10 mg of each material was added to 10 mL of a 20 ng / mL methamphetamine solution and shaken on a vortexer. The supernatant was taken at different times for testing, and the adsorption curves at different time points were calculated based on the ultra-high performance liquid chromatography-tandem mass spectrometry UPLC-MS-MS results.

[0086] Figure 4 This is the adsorption curve of different materials during the preparation process of Example 1 of this application. Figure 4 As shown, after 2 hours of shaking, the adsorption amount of methamphetamine target molecules by Fe3O4@mSiO2@bAu nanopocket structure was 190 ng, and the adsorption efficiency was 95%.

[0087] Similarly, the adsorption amounts of the Fe3O4@mSiO2@bAu nano-pocket structure prepared in Examples 2-4 for the methamphetamine target molecule were 185ng, 188ng, and 180ng, respectively, and the corresponding adsorption efficiencies were 92.5%, 94%, and 90%, respectively. It can be seen that the adsorption efficiency of the Fe3O4@mSiO2@bAu nano-pocket structure in this application for the methamphetamine target molecule reaches more than 90%, indicating that the pores of the nano-pocket structure have the ability to capture the methamphetamine target molecule.

[0088] Example 6

[0089] Detection of drugs of different concentrations (methamphetamine, α-methyltryptamine and etonizine) based on the nano-pocket structure. See the schematic diagram of the detection process. Figure 5 .like Figure 5 As shown in the figure, the Fe3O4@mSiO2@bAu nanomaterial prepared in Example 1 was uniformly dispersed into drug solutions containing different concentrations (1x 10 -3 M, 1x 10 -5 M, 1x 10 -7 M, 1x 10-8 M, 1x 10 -9 M) and shaken for 2 hours. The obtained nanoparticles were collected magnetically and placed on a glass slide to dry naturally, and then analyzed and detected by Raman spectrometer, and the relationship between Raman signal intensity and drug concentration was fitted to the corresponding curve. The dispersion concentration of the Fe3O4@mSiO2@bAu nanomaterial was 0.2mg / mL.

[0090] Figure 6 The SERS spectra of the nano-pocket structure in Example 1 of the present invention are as follows: Figure 6 As shown in the first column (a, e, i), (a, e, i) are the Raman detection intensities of methamphetamine, α-methyltryptamine and edonisine at different concentrations, and the detection limits are all 1x 10 -9 M, achieving high sensitivity detection of drugs. Figure 6 As shown in (b, f, j), this detection method can detect methamphetamine at 1003 cm -1 The Raman signal at the 2 =0.989), for α-methyltryptamine at 758 cm -1 The Raman signal at the 2 =0.999), p-etonirazine at 1337 cm -1 The Raman signal at the 2 =0.998).

[0091] Example 7

[0092] Based on the uniformity and stability of the nano-pocket structure in Example 1.

[0093] The solution concentration in Example 6 was 1x 10 -3 M methamphetamine detection sample randomly selected 30 points for Raman detection, 30 Raman signal intensities were plotted and data analyzed, such as Figure 6 As shown in (c, g, k), the relative standard deviations of methamphetamine, α-methyltryptamine, and etonizine were all less than 6%, indicating that the prepared materials had good uniformity and the detection method had excellent reliability. Figure 6 (d, h, i) show that the concentration of the solution in Example 6 is 1x 10 -3 The Raman signal stability of the methamphetamine detection samples was tested, and the results showed that after two months of storage, the Raman signal intensity only decreased by 10%, indicating its good stability.

[0094] In summary, the nano-pocket structure designed by the present invention for capturing target molecules is easy to synthesize and has the ability to capture target molecules to the Raman enhanced hotspot area, thereby achieving the purpose of high-sensitivity drug detection; in addition, the material also exhibits good stability and uniformity, providing strong support for public security anti-drug work.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application. Those skilled in the art should understand that, although the present application is described in detail with reference to the aforementioned embodiments, the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions in the embodiments of the present application.

Claims

1. A nano-pocket structure for capturing target molecules, characterized in that: The invention comprises magnetic ferrosoferric oxide particles as a substrate and a mesoporous silica layer with multiple silanol groups coated on the outside of the substrate; wherein nano-gold branches are loaded in the pores of the mesoporous silica.

2. The nano pocket structure according to claim 1, characterized in that: The particle size of the magnetic ferroferric oxide particles is in the range of 50 to 500 nm, and the thickness of the mesoporous silica is in the range of 10 to 150 nm.

3. The nano pocket structure according to claim 1, characterized in that: Nano-gold colloid particles are adsorbed on the surface of the magnetic ferroferric oxide particles, and the nano-gold branches are obtained by growing the nano-gold colloid particles as gold seeds in the mesoporous silica channels.

4. The nano pocket structure according to claim 3, characterized in that: The particle size of the nano gold colloid particles ranges from 3 to 15 nm.

5. A method for preparing a nano-pocket structure for capturing target molecules, characterized in that: The following steps are involved: Step 1: preparing Fe3O4@PEI nanomaterials: adding Fe3O4 magnetic particles to a polyethyleneimine aqueous solution, and subjecting the solution to ultrasonic reaction to allow polyethyleneimine to self-assemble on the surface of the Fe3O4 magnetic particles to form Fe3O4@PEI particles; Step 2, preparing Fe3O4@Au nanomaterials: adding Fe3O4@PEI nanomaterials into nano-gold colloids, and ultrasonically reacting the nano-gold colloids to adsorb the colloidal gold particles onto the surface of the Fe3O4@PEI particles, thereby obtaining Fe3O4@Au nanomaterials; Step 3, preparing Fe3O4@Au@mSiO2 nanomaterials: ultrasonically disperse the Fe3O4@Au nanomaterials into a hexadecyltrimethylammonium bromide aqueous solution, slowly drop tetraethyl silicate after adding alkali, react for 24 hours after the addition is completed, separate by magnetic adsorption, and wash the solids three times with water and ethanol respectively; disperse the obtained solids in a template removal solution and stir for 8 hours, and repeat the operation several times to obtain Fe3O4@Au@mSiO2 nanomaterials; Step 4. Preparation of Fe3O4@mSiO2@bAu nanomaterials: Ultrasonic dispersion of Fe3O4@Au@mSiO2 nanomaterials in water, adding chloroauric acid solution and dilute hydrochloric acid, followed by silver nitrate solution and ascorbic acid solution, reacting at room temperature, separating by magnetic adsorption, and then washing the solid three times with water and ethanol respectively.

6. The method according to claim 5, characterized in that The Fe3O4 magnetic particles in step 1 are prepared by solvent thermal synthesis, with a particle size range of 50 to 500 nm; the concentration of the polyethyleneimine aqueous solution is 0.1% to 1%; and the ultrasonic reaction time is 10 to 60 minutes.

7. The method according to claim 5, characterized in that The size of the nano-gold colloid particles in step 2 is 3 to 15 nm; and the ultrasonic reaction time is 10 to 60 minutes.

8. The method according to claim 5, characterized in that The concentration of the aqueous solution of hexadecyltrimethylammonium bromide in step 3 is 0.01% to 1%; the base includes any one of triethylamine, 25% ammonia water, 15% ammonia water, 5% ammonia water, triethanolamine, 0.1M sodium hydroxide, 0.5M sodium hydroxide, and 1M sodium hydroxide; The weight of tetraethyl silicate is 5 to 100 times that of Fe3O4@Au nanomaterial; the reaction temperature is 25 to 100 degrees; The template removal solution is ethanol, 1% HCl / ethanol, 1% NaCl / methanol, 0.6% ammonium nitrate solution or acetone, and the number of times of template removal is 5 to 8 times.

9. The method according to claim 5, characterized in that The concentration of the chloroauric acid solution in step 4 is 0.1M-1M; the concentration of the dilute hydrochloric acid is 0.1M-2.5M; the concentration of the silver nitrate solution is 1mM-10mM; the concentration of the ascorbic acid solution is 0.05M-1M; and the reaction time is 10-60min.

10. Use of the nano-pocket structure according to any one of claims 1 to 4 in detecting drugs using Raman spectroscopy.